2022
DOI: 10.1186/s40862-022-00135-8
|View full text |Cite
|
Sign up to set email alerts
|

Online self-evaluation: the EFL writing skills in focus

Abstract: Students need more independent roles to evaluate their learning performance, especially in the absence of teachers’ feedback due to some constraints such as technology and poor experience. This study investigates the potential of online self-evaluation on students’ writing skills in English as a foreign language (EFL). It examines the preparatory year (PY) level one students’ most improved EFL writing areas and perceptions when they use online self-evaluation in writing. In this quasi-experiment, two groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, MF reported that she had never obtained either "basic" or "advanced" training. However, student's writing abilities can greatly benefit from the application of the strategy of self-evaluation and use rubrics in scoring (Al-Mwzaiji & Alzubi, 2022;Mahasneh, 2020;Meihami & Varmaghani, 2013;Rehm et al, 2021;Wambsganss et al, 2022). The assertion was supported by the opinions of more than half of the teachers.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, MF reported that she had never obtained either "basic" or "advanced" training. However, student's writing abilities can greatly benefit from the application of the strategy of self-evaluation and use rubrics in scoring (Al-Mwzaiji & Alzubi, 2022;Mahasneh, 2020;Meihami & Varmaghani, 2013;Rehm et al, 2021;Wambsganss et al, 2022). The assertion was supported by the opinions of more than half of the teachers.…”
Section: Discussionmentioning
confidence: 96%
“…The use of ICT in EFL learning has contributed wonderful benefits in language acquisition, practice, and utilization (Al-Mwzaiji & Alzubi, 2022). The knowledge of ICT and Internet connectivity must be utilized for the exposure of Saudi EFL learners to native and non-native English speakers around the world.…”
Section: The Strategic Steps Of Improvement To Fulfill Saudi Vision 2...mentioning
confidence: 99%
“…To ensure the effective use of self-evaluation strategies, direct instruction on how to use the tools is critical. For example, students must know what the tool for self-evaluating is, how to use it, and then have practice opportunities to help form an understanding of writing knowledge, to increase awareness of mistakes, and to effectively self-evaluate their writing (Al-Mwzaiji & Alzubi, 2022).…”
Section: Digital Tools To Support Self-evaluationmentioning
confidence: 99%